Thromboelastography Variables, Immune Markers, and Endothelial Factors Associated With Shock and NPMODS in Children With Severe Sepsis - Saini, Arun; Spinella, Philip C.; Ignell, Steven P.; Lin, John C. (Frontiers in Pediatrics, 2019)
Objective: Evaluate hemostatic dysfunction in pediatric severe sepsis by thromboelastography (TEG) and determine if TEG parameters are associated with new or progressive multiple organ dysfunction syndrome (NPMODS) or shock, defined as a lactate ≥ 2mmol/L. We explored the relationship between TEG variables, selective cytokines, and endothelial factors. Design: Prospective observational. Setting: Single-center, quaternary care pediatric intensive care unit. Patients: Children aged 6- months to 14- years with severe sepsis with expected PICU stay for >72 hours. Interventions: None. Measurements and Main Results: Twenty-eight children were enrolled with median (IQR) age of 7.3 years (4.4-11.4), PELOD score (study day-1) of 11(1.25-13), and PICU length of stay of 10 days (5-28). TEG-defined hypercoagulable state occurred most commonly in 73% (94/129) of samples, followed by hypocoagulable state in 7.8% (10/129) and mixed coagulation state in 1.5% (2/129) of samples in the study cohort. In contrast, hypocoagulable state occurred most commonly in 66% (98/148) of samples based on standard coagulation parameters. In the 7 children who developed shock with NPMODS compared to 8 patients with shock without NPMODS and 12 patients with severe sepsis only, we found more profound coagulopathy [thrombocytopenia (p= 0.04), elevated INR (p= 0.038), low fibrinogen level (p= 0.049), and low TEG-G value (p= 0.01)] and higher peak of interleukin-6 (p= 0.0014) and IL-10 (p= 0.007). Peak lactate in the first 5 study days had moderate correlation with standard coagulation assays, TEG parameters, and selective cytokines. Peak lactate did not correlate with markers of endothelial activation. Lowest TEG -G value had moderate correlation with peak IL-10 (ρ -0.442, p= 0.019), peak VCAM (ρ -0.495, p= 0.007), and peak lactate (ρ -0.542, p= 0.004) in the first 5 study days. A combination of TEG-G value and IL-6 concentration best discriminated children with shock and NPMODS (AUC 0.979 (95%CI 0.929-1.00), p< 0.001). Conclusion: This exploratory analysis of hemostasis dysfunction on TEG in pediatric severe sepsis suggests that while hypercoagulability is more common, a hypocoagulable state is associated with shock and NPMODS. In addition, TEG abnormalities are also associated with immune and endothelial factors. A larger cohort study is needed to validate these findings.